Penerapan cognitive stimulation therapy untuk meningkatkan kapasitas memori pada lansia dengan demensia di panti - Yulia Yunara; Herawati; Aditya Anin Primasari; Muhammad Nur Fajri (Universitas Sanata Dharma, 2026)
Dementia is a progressive neurocognitive disorder characterized by declining memory, language abilities, and the capacity to perform daily activities. In the absence of effective pharmacological therapies, non-pharmacological interventions–particularly cognitive stimulation–have become essential strategies for maintaining cognitive function and enhancing the quality of life among older adults. This community-service program aimed to implement and evaluate a picture-guessing activity as a form of cognitive stimulation for older adults with dementia in long-term care facilities. The program was conducted in small-group sessions using image cards depicting familiar objects and everyday activities, with sessions lasting 45–60 minutes over the course of one week. Evaluation results demonstrated an increase in the mean Mini-Mental State Examination (MMSE) score from 19.8 to 22.3 and in the Montreal Cognitive Assessment (MoCA) score from 17.2 to 19.4 following the intervention. A significant difference was confirmed using the Wilcoxon Signed-Rank Test (p = 0.027 < 0.05). In addition, participants showed improvements in attention, naming ability, and social participation. The picture-guessing program proved to be simple, low-cost, and effective as a cognitive-stimulation approach for older adults with dementia in a social-care setting, and it holds strong potential for broader adaptation to support the well-being and quality of life of the elderly population.